Identification of specific histidines as pH sensors in flavivirus membrane fusion - Fritz, Richard (The Rockefeller University Press, 2008)
The flavivirus membrane fusion machinery, like that of many other enveloped viruses, is triggered by the acidic pH in endosomes after virus uptake by receptor-mediated endocytosis. It has been hypothesized that conserved histidines in the class II fusion protein E of these viruses function as molecular switches and, by their protonation, control the fusion process. Using the mutational analysis of recombinant subviral particles of tick-borne encephalitis virus, we provide direct experimental evidence that the initiation of fusion is crucially dependent on the protonation of one of the conserved histidines (His323) at the interface between domains I and III of E, leading to the dissolution of domain interactions and to the exposure of the fusion peptide. Conserved histidines located outside this critical interface were found to be completely dispensable for triggering fusion.